EFEKTIVITAS MODEL PEMBELAJARAN PJBL DENGAN PENDEKTAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF SISWA MATERI TATA SURYA - Triyani Rasyiida, Gadis; Rosmiati; Ladyawati, Erlin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Project-Based Learning (PJBL) model with a Deep Learning approach on enhancing students' reflective thinking skills in the Solar System topic at the elementary school level. Science education at the elementary level often still revolves around teacher-centered methods and conventional approaches, which tend to limit students' active involvement in the learning process. One solution to improve the quality of learning is by implementing a project-based learning model that focuses on students as the center of learning, providing opportunities for them to engage in real-world projects that deepen their understanding of the concepts being studied. The PJBL model integrated with the Deep Learning approach offers students the chance to not only learn the material in depth but also to reflect on their learning process and outcomes, an essential aspect in developing higher-order thinking skills. This research was conducted at SDN Dukuh Kupang II Surabaya using an experimental design involving two student groups: an experimental group applying the PJBL model with a Deep Learning approach and a control group using conventional learning methods. Data were collected through reflective thinking tests in the form of pretest and posttest scores, as well as a questionnaire to measure students' responses to the learning process. The results show a significant improvement in students' reflective thinking skills in the experimental group compared to the control group, as reflected in the high NGain scores on the posttest. Furthermore, students' responses to this learning model were overwhelmingly positive.